2017
DOI: 10.4236/nr.2017.810042
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Stream Pathogenic Indicator Bacteria Concentrations in Livestock Grazing Areas across a Single National Forest

Abstract: Livestock presence in proximity to forest streams has been shown to contribute pathogenic bacteria in excess of water quality standards established to protect human health. However, the degree to which livestock fecal contamination in streams on national forest lands is either a limited or a potentially widespread occurrence is still debated. This study provides additional insight into the matter. We analyzed water in small streams near known cattle grazing areas within the Stanislaus National Forest in the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…An explanation for this result is that regardless of stocking rate or rotational treatment, E. coli levels were high on the days cattle were present. (Myers et al, 2017;O'Callaghan et al, 2019). By tracking water quality in relation to regulatory benchmarks across an entire grazing season, and including gradients of duration and timing in our study design, we show that fewer water quality violations occurred when grazing periods were short, and when grazing occurred early or late in the season.…”
Section: Using Duration and Timing To Manage Ecosystem Service Trade-offsmentioning
confidence: 78%
“…An explanation for this result is that regardless of stocking rate or rotational treatment, E. coli levels were high on the days cattle were present. (Myers et al, 2017;O'Callaghan et al, 2019). By tracking water quality in relation to regulatory benchmarks across an entire grazing season, and including gradients of duration and timing in our study design, we show that fewer water quality violations occurred when grazing periods were short, and when grazing occurred early or late in the season.…”
Section: Using Duration and Timing To Manage Ecosystem Service Trade-offsmentioning
confidence: 78%
“…Restricting livestock manure entering into streams is considered to be effective in controlling bacteria loads to streams (Gotkowska‐Płachta et al, 2016; Myers et al, 2017; Pachepsky et al, 2016; Soupir et al, 2006). However, additional measures may be needed for reducing the levels of sediment‐attached bacteria in a stream.…”
Section: Resultsmentioning
confidence: 99%
“…There has been increased concern regarding the impacts of cattle activity near or in watercourses (Muenz et al, 2006; Vidon et al, 2008; Wilson and Everard, 2017), and the practice of allowing unrestricted cattle access to watercourses has been discouraged in some areas including North America and Europe (Bremner et al, 2016; Bragina et al, 2017; Myers et al, 2017). In an effort to reduce the potential environmental impact of cattle access to watercourses, a variety of optional and compulsory mitigation measures are typically available to landowners under agri‐environmental policies.…”
Section: A Synopsis Of Studies Examining the Impact Of Cattle Exclusimentioning
confidence: 99%
“…Several authors have reported increased fecal contamination in streams impacted by cattle grazing and activity. For instance, Myers et al (2017) assessed the levels of E. coli in watercourses draining areas used for dairy cattle grazing in California, USA, in periods of cattle presence and absence and reported 194 cases of violation of either regional or federal regulatory standards for E. coli in recreational waters, all documented when cattle were present in the grazing fields. The authors observed that E. coli concentrations in waters were generally orders of magnitude higher when cattle were grazing the fields compared with a period of cattle absence (Myers et al, 2017).…”
Section: In‐stream and Sediment Pathogenic Microbesmentioning
confidence: 99%
See 1 more Smart Citation